Umbilical Artery Embolism: A Case Report and Literature Review. Issue 4 (16th October 2021) - Zhang, Qinjian; Fang, Zhuanji; Chen, Siwen; Xu, Xia; Yan, Jianying
Abstract : Abstract: Umbilical cord (UC) embolism is a rare, life-threatening complication of pregnancy. The exact cause of this condition is not yet known. Women with more than one UC abnormality are at risk of UC obstruction; this condition can lead to stasis, ischemia, and in some cases, thrombosis. However, many women with UC abnormalities remain undetected and may not be recognized until after birth. Here, we present a case involving the prenatal diagnosis and successful treatment of umbilical artery embolism in the third trimester with good maternal and fetal outcomes. The risk of UC embolism increases when more than one UC abnormality is identified in a single case. Ultrasound examination in the third trimester of pregnancy should be able to verify the existence of two arteries and one vein in the UC. If necessary, these results can be compared with ultrasound imaging acquired during the first trimester of pregnancy.